2020
DOI: 10.1007/s42729-020-00321-y
|View full text |Cite
|
Sign up to set email alerts
|

Combined Soil and Foliar Nitrogen Fertilization Effects on Rainfed Almond Tree Performance

Abstract: Cultivation of almond in the Mediterranean region is traditionally done under rainfed conditions and poorly established cropping practices resulting in low yields. Despite the importance of nitrogen (N) fertilization to increase yield in cultivated species, this practice is usually neglected in rainfed managed almond orchards. Selection of the most appropriate rate and method of nitrogen (N) application are utmost factors to maximize almond yield in the considered conditions. Therefore, the aim of this study w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 37 publications
2
7
0
Order By: Relevance
“…In Hazelnut B + Zn applications increased nut size and kernel weight (Horuz et al, 2021). In almond, soil and foliar N applications did not significantly affect the nut and kernel weight (Morais et al, 2020). A somewhat similar finding was obtained in this current study.…”
Section: Fruit Properties and Yieldsupporting
confidence: 91%
See 1 more Smart Citation
“…In Hazelnut B + Zn applications increased nut size and kernel weight (Horuz et al, 2021). In almond, soil and foliar N applications did not significantly affect the nut and kernel weight (Morais et al, 2020). A somewhat similar finding was obtained in this current study.…”
Section: Fruit Properties and Yieldsupporting
confidence: 91%
“…A similar result was achieved in this study. In the research by Morais et al, (2020) investigating the effects of combined soil and foliar nitrogen fertilization applications on almond trees, it was stated that N fertilization was not effective yield. On the contrary, in the current study, an increase in yield was recorded with foliar N application compared to the control in both locations and years.…”
Section: Fruit Properties and Yieldmentioning
confidence: 99%
“…In addition, if the water loss due to transpiration exceeds the amount of water taken up by the roots, the tree can exhibit stress responses, starting with stomatal closure. This will produce a reduction in gas exchange, with subsequent decreases in the rates of photosynthesis and the production of carbohydrates ( Morais et al, 2020 ), limiting the amount of energy available for vegetative growth, but also the transport of mineral nutrients, such as B, that move through the flow of water.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, a researcher found that application of N to the soil influenced the physiological performance of almond trees with positive implications on yield, while the supply of N via foliar fertilization (0.5% N applied three times during the growing season) did not provide encouraging results since it failed to improve the physiological behavior and yield of almond (Morais et al, 2020). Thus, other researcher explained that leaf sprays of N and B, including post-harvest applications, failed to increase crop nutritional status and kernel yield (Arrobas et al, 2019).…”
Section: Resultsmentioning
confidence: 99%